Conflict in the Holy Land : from ancient times to the Arab-Israeli conflicts - DiPrizio, Robert C., 1968- (ABC-CLIO, 2020)
"With more than 200 cross-referenced entries covering every aspect of conflict in the Holy Land, this illuminating book will help students understand the volatile history of Palestine and Israel and its impact on the rest of the world"--Provided by publisher.